2017
DOI: 10.5812/jjm.14379
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factor and Biofilm Formation in Clinical Enterococcal Isolates of the West of Iran

Abstract: Background: Enterococcus spp., a part of the normal flora of the human intestine, possess several virulence factors that can develop biofilms to endure harsh environments. Their ability to cause nosocomial infections makes them as critical opportunistic pathogens in hospital settings. Objectives: The current study aimed at determining the occurrence of 6 genes coding virulence factors and their ability to develop biofilms, and conducting phenotypical assessments of haemolysin and gelatinase in clinical enteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
3
8
1
Order By: Relevance
“… 30 , 39 , 40 Despite this high frequency of detection of gelE , only 22% of the isolates expressed a phenotypic gelatinase activity, consistent with prior findings. 18 , 41 Other studies stated that expression of gelE is regulated by the fsr locus and does not merely depend on gelE , 15 , 42 which is congruent with our findings here, as a significant and strong correlation between the presence of fsrA, fsrB, fsrC and the gelatinase activity was found. As in prior work from our laboratory, 18 fsrA or fsrB can be a sufficient biomarker for gelatinase activity; however, fsrB remains the single strongest predictor ( Figure 3 and Table 4 ) of that activity.…”
Section: Discussionsupporting
confidence: 92%
“… 30 , 39 , 40 Despite this high frequency of detection of gelE , only 22% of the isolates expressed a phenotypic gelatinase activity, consistent with prior findings. 18 , 41 Other studies stated that expression of gelE is regulated by the fsr locus and does not merely depend on gelE , 15 , 42 which is congruent with our findings here, as a significant and strong correlation between the presence of fsrA, fsrB, fsrC and the gelatinase activity was found. As in prior work from our laboratory, 18 fsrA or fsrB can be a sufficient biomarker for gelatinase activity; however, fsrB remains the single strongest predictor ( Figure 3 and Table 4 ) of that activity.…”
Section: Discussionsupporting
confidence: 92%
“…It was determined gelatinase enzymatic activity is a prerequisite for biofilm formation (19). In previous studies, gelE positivity varies between 19.6 % and 80.4 % (14,18,20,21). In this study gelE gene positivity was observed at 22.8 %, and ampicilin resistance in gelE gene positive E. faecalis was significantly higher compared to isolates that did not contain these genes.…”
Section: Discussionmentioning
confidence: 48%
“…Nevertheless, the presence of virulence determinants in the clinical isolates might contribute to increased severity as they could be expressed under optimum conditions in vivo. Metadata of the previous studies on the detection of virulence genes of enterococci by multiplex/duplex/simplex PCR is depicted in Additional file 1: Table S1 [18,27,29,[33][34][35][36][37][38][39][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%